1995
DOI: 10.1002/lipi.19950970905
|View full text |Cite
|
Sign up to set email alerts
|

TLC Separation of Glucopyranosyl Sinapate and Other Phenolic Compounds from Rapeseed

Abstract: R. A m a r o w i c z , M . K a r a m a c ' , B. R u d n i c k a a n d E . C i s k a *Glucopyranosyl sinapate was obtained from rapeseeds using column chromatography on Sephadex LH-20 and RP-18 semipreparative HPLC. TLC analysis of this compound, sinapic acid and phenolic compounds fractions from column chromatography were conducted on plates coated with silica gel (standard and HPTLC), with cellulose and on RP-TLC plates. Eleven various solvent systems were applied to develop chromatograms. HPTL plates were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Accumulation of phenylpropanoids in cotyledons of Pharbitis nil strain Violet seedlings during the induction of flowering by poor nutrition was observed (Hairai et al, 1993). Glucopyranosyl sinapate was obtained from rapeseeds (Amarowicz et al, 1995). Characterization of Some Blood Orange Varieties Using Polyphenol Profiles.…”
Section: Resultsmentioning
confidence: 99%
“…Accumulation of phenylpropanoids in cotyledons of Pharbitis nil strain Violet seedlings during the induction of flowering by poor nutrition was observed (Hairai et al, 1993). Glucopyranosyl sinapate was obtained from rapeseeds (Amarowicz et al, 1995). Characterization of Some Blood Orange Varieties Using Polyphenol Profiles.…”
Section: Resultsmentioning
confidence: 99%
“…Zadernowski (1987) found that flours obtained from Polish rapeseed varieties contained from 0.16 to 0.65 mmol of phenolic acid glycosides per kilogram of flour. The compound 1-O-β-D glucopyranosyl sinapate is the predominant glycoside in rapeseed and canola varieties Amarowicz et al, 1995;Wanasundara et al, 1994).…”
Section: Esterified Phenolic Acidsmentioning
confidence: 99%
“…The content of phenolic compounds was determined by Folin-Ciocalteu method (29). The composition of phenolic compounds was determined by thin layer chromatography (TLC) on CAMAG TLC Scanner 4 (Muttenz, Switzerland) apparatus equipped with automatic TLC (30). The sinapine and sinapic acid were identified by comparing the R f value (distance eluent travels was 10 cm) of the standard substances.…”
Section: Determination Of Chemical Composition Of the Inhibitormentioning
confidence: 99%